جماليات النص الشعري في ديوان "على جناح نورس" لعبد المولى الغدادي: دراسة أسلوبية - Khalifah Ahnin Muhammad Abu Khalidah
Libyan literature in poetry and prose is still open for analytical and critical studies, to discover its technical characteristics. Abdel Mawla al-Baghdadi's Diwan "Ala Jannah Nawras: On the wing of a Seagull" is just an example like any other Libyan literary work. This Diwan was subjected to three studies, none of them adopted a Stylistic study. The main objective is to figure out the stylistic phenomena in al-Baghdadi texts, according to critic's foundations. The researcher depends Descriptive Analytical method. Chapter one trends and implications of Al- Baghdadi Poetry. Chapter I1 sounds features styles. Chapter I11 the Linguistic stylistic features. Chapter IV Al- Baghdadi style and its impact. The findings revealed that; Al- Baghdadi Poetry was a very beautiful that brought together the Emotional, Religious, Social and Political poetry. He also said love poetry to homeland. Innovation was achieved in the use of music due to his psychological state; as well as text cohesion and coherence. Besides the use of sentences deviation toward the front and back, deletion, emphasis, query, fixed and denial that all were contributed to the function of poetry. Phrases from the poet's memories in a beautiful and wonderful images. The researcher recommended that further studies on the Libyan literature is required to disclose its Aesthetics; To achieve an appropriate reputation within the Arab and world literatures. Study the Libyan literary production through stylistic studies, to follow the poetic text accurately at all levels, which reflect the poet's thought and his vision inside the texts.